MBA dissertation through business study mission : transportation and tourism sectors in Western Canada-British Columbia and Alberta. - Lim, Eric Eng Kiat. (2010)
Western Canada is transforming from an "old economy" highly reliant on forestry and mining to a "new economy" largely dependent on high-tech industries, knowledge-based sectors and tourism. Our dissertation aims to highlight the growth potential of the tourism industry globally, Canada-wide and specifically in British Columbia and Alberta and the tourism products they offer to visitors year-round. An exploration of the tourism industry cannot be complete without a thorough discussion of the transportation infrastructure. A country may have a transportation sector without tourism, it cannot have a tourism sector without transportation. The study explains the transportation sector in Canada and the vital role it plays in both freight and passenger services.